ANALISIS PROBLEMATIKA PROFESIONALISME GURU TERHADAP KEMAJUAN PROGRAM SUPERVISI PENDIDIKAN DI MADRASAH IBTIDAIYAH WILAYAH JAWA TIMUR - Yaqin, Achmad Haqqul; Munawir, Munawir; Jannah, Miftakhul; Faizah, Arista Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI), 2024)
As a teacher, of course, you cannot avoid the problems that occur, one of which is the problem of professionalism in the progress of educational supervision in schools. This study aims to find out the problems that often occur in teacher professionalism towards the progress of an educational supervision program in each educational unit, especially at the SD/MI level. With the results obtained, it is necessary to develop teacher professionalism in educational supervision programs by adjusting to science, technology, and socio-economic conditions in society. From the known problems, the researchers also provided several solutions or suggestions to be able to support the progress of the educational supervision program at the SD/MI level. This can make it easier for educational units to implement it as well as possible for teachers. Every teacher who is professional, then this will have an impact on the progress of each educational unit. The quality of a good workforce will affect the quality of the educational unit occupied.